2023
DOI: 10.1097/hjh.0000000000003391
|View full text |Cite
|
Sign up to set email alerts
|

A candidate locus in the renalase gene and susceptibility to blood pressure responses to the dietary salt

Abstract: Background: High dietary salt confers a risk of elevating blood pressure (BP) and the development of hypertension. BP to salt intake may be determined in part by individual genetic predisposition. Identifying these genetic underpinnings will enhance our understanding of the biological mechanisms of BP regulation. This study aims to assess the genetic association with salt sensitivity of BP (SSBP) within two well-phenotyped multinational cohorts. Methods: A total of 720 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…It was the only significant association with the cardiometabolic cluster. RNLS is highly expressed in the heart and contributes to regulating blood pressure (43). In genetic association studies, RNLS has been previously associated with type 1 diabetes (44) and smoking initiation (45).…”
Section: Discussionmentioning
confidence: 99%
“…It was the only significant association with the cardiometabolic cluster. RNLS is highly expressed in the heart and contributes to regulating blood pressure (43). In genetic association studies, RNLS has been previously associated with type 1 diabetes (44) and smoking initiation (45).…”
Section: Discussionmentioning
confidence: 99%
“…confirmed RNLS as a potential target for β cell protection in T1D, aiming to mitigate immune recognition of β cells ( 63 ). RNLS, responsible for degrading circulating catecholamines and regulating blood pressure ( 152 ), was first discovered as a susceptible factor in autoimmune destruction of pancreatic β cells through a GWAS study of monocytes, including their derivatives, such as macrophages and dendritic cells, from T1D patients ( 153 ). Cai et al.’s study demonstrated that RNLS deletion did not affect the ability of iPSCs into β cells and secrete insulin ( 63 ).…”
Section: T1dmentioning
confidence: 99%
“…In human studies, by selecting 720 participants from the HyperPATH consortium program and genotyping with the use of a multiethnic genotyping array of their renalase (RNLS) gene, the research group of Heydarpour et al determined that certain genetic variants of the RNLS gene associated with salt sensitivity of blood pressure and responded to dietary salt intervention [42]. Many other studies also confirm a decrease in blood renalase concentration caused by the influence of a high-salt diet [43][44][45].…”
Section: Dietmentioning
confidence: 99%